2019
DOI: 10.1101/759969
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-throughput isolation and sorting of gut microbes reduce biases of traditional cultivation strategies

Abstract: Traditional cultivation approaches in microbiology are labor-intensive, low-throughput, and often yield biased sampling of taxa due to ecological and evolutionary factors. New strategies are needed to enable ample representation of rare taxa and slow-growers that are outcompeted by fast-growing organisms. We developed a microfluidic platform that anaerobically isolates and cultivates microbial cells in millions of picoliter droplets and automatically sorts droplets based on colony density. We applied our strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
(65 reference statements)
1
4
0
Order By: Relevance
“…1C). This finding is consistent with the hypothesis that droplet isolation enables slowgrowing microbes to be sheltered from competition with fast-growing bacteria (18,24,31).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1C). This finding is consistent with the hypothesis that droplet isolation enables slowgrowing microbes to be sheltered from competition with fast-growing bacteria (18,24,31).…”
Section: Resultssupporting
confidence: 90%
“…Because droplets are not limited by the need to microfabricate physical wells or channels, millions of distinct culture volumes can be created in minutes. So far, droplet techniques have been used to isolate uncultured microbes from seawater, soil, and gut communities (18,(22)(23)(24); assess microbial cross-feeding (25); track population dynamics of individual bacteria (26); and examine antibiotic sensitivity and commensal-pathogen interactions of human gut and oral microbiota (27,28). Still, existing droplet microfluidic approaches for assaying bacteria have required combining complex emulsion techniques (water-oil-water) with the use of flow cytometers or custom on-chip droplet sorting devices.…”
mentioning
confidence: 99%
“…While we used dynamic droplet incubation to continuously supply the droplet population with oxygen, the perflourinated oil carrying the dissolved gases could also be charged with nitrogen or other gases to enable a microaerophilic or even anaerobic incubation. It was recently shown that the anaerobic incubation of human microbiomes in droplets increases the species richness dramatically 21,22 . Besides encapsulating single cells, several cells could be confined per droplet creating simplified multispecies communities, which have the potential to either support growth of dependent species 44 or to exert a change in natural product biosynthesis 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…A complementary trend is the miniaturization of the culture vessels 12,14,[18][19][20][21][22][23][24][25][26][27][28][29][30] to save material and time while increasing the throughput and thereby the chance to find non-dormant, culturable variants of naturally occurring species. These microscale culture techniques have the idea in common to partition complex bacterial communities on the single cell level, allowing the various species to grow at their own speed, since they do not have to compete neither for space nor for nutrients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation